Regional Power Transitions: Lessons from the Southern Cone - Luis Leandro Schenoni (German Institute of Global and Area Studies (GIGA), 2016)
Approximately four decades ago, the Southern Cone witnessed the beginning of a transition from a bipolar balance of power between Argentina and Brazil to unipolarity under Brazilian primacy. While such processes are expected to generate conflict, this particular transition was cooperative, leaving an interesting IR puzzle unresolved: Why did Argentina stop counterbalancing Brazil and opt for accommodation instead? Building on power transition theory, I use process tracing to show that key cooperative turns in this bilateral relationship - during the late 1970s and early 1990s - were possible only after social coalitions were redefined in Argentina. My conclusions suggest that cooperation between Argentina and Brazil was not a product of democracy but rather a consequence of structural changes, at both the international and the domestic level.
Keywords: 300; Brazil; Argentina; Southern Cone; power transition